2016
DOI: 10.1074/jbc.m116.749150
|View full text |Cite
|
Sign up to set email alerts
|

Unorthodox Acetylcholine Binding Sites Formed by α5 and β3 Accessory Subunits in α4β2* Nicotinic Acetylcholine Receptors

Abstract: All nicotinic acetylcholine receptors (nAChRs) evolved from homomeric nAChRs in which all five subunits are involved in forming acetylcholine (ACh) binding sites at their interfaces. Heteromeric ␣4␤2* nAChRs typically have two ACh binding sites at ␣4/␤2 interfaces and a fifth accessory subunit surrounding the central cation channel. ␤2 accessory subunits do not form ACh binding sites, but ␣4 accessory subunits do at the ␣4/␣4 interface in (␣4␤2) 2 ␣4 nAChRs. ␣5 and ␤3 are closely related subunits that had been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 47 publications
(70 reference statements)
1
28
0
Order By: Relevance
“…These studies concluded that (α4) 2 (β2) 3 nAChRs showed high sensitivity (HS) to agonists ligands, whereas those with an (α4) 3 (β2) 2 stoichiometry showed low sensitivity (LS). It has also been shown that a 3rd noncanonical ligand‐binding site is present between the α4–α4 interface of the (α4) 3 (β2) 2 LS stoichiometry, the α5–α4 interface of the (α4) 2 (β2) 2 α5 subtype, and the β3–α4 interface in the (α4) 2 (β2) 2 β3 subtype . Interestingly, some agonist ligands are excluded from these noncanonical sites.…”
Section: Nachr Subtypes Display Different Sensitivities To Ligandsmentioning
confidence: 99%
“…These studies concluded that (α4) 2 (β2) 3 nAChRs showed high sensitivity (HS) to agonists ligands, whereas those with an (α4) 3 (β2) 2 stoichiometry showed low sensitivity (LS). It has also been shown that a 3rd noncanonical ligand‐binding site is present between the α4–α4 interface of the (α4) 3 (β2) 2 LS stoichiometry, the α5–α4 interface of the (α4) 2 (β2) 2 α5 subtype, and the β3–α4 interface in the (α4) 2 (β2) 2 β3 subtype . Interestingly, some agonist ligands are excluded from these noncanonical sites.…”
Section: Nachr Subtypes Display Different Sensitivities To Ligandsmentioning
confidence: 99%
“…Recently, a third ACh site was identified at the α4/α4 subunit interface in (α4β2) 2 α4 nAChRs (Harpsoe et al , ; Mazzaferro et al , ). Subsequently, additional ACh sites were found at α5/α4, β3/α4 and α4/α5 subunit interfaces (Jin et al , ; Wang et al , ; Jain et al , ). These sites are referred to as unorthodox sites.…”
Section: Introductionmentioning
confidence: 99%
“…Subunit interfaces that form ACh‐binding sites are noted. α5 and β3 subunits form an ACh‐binding site with α4 subunit (Jain et al , ), and it is to be determined whether they do so with other α subunits. (B) Illustration of different stoichiometric forms of (α4) 2 (β2) 2 α5 expressed from subunit concatamers (Jain et al , ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations